EPC Minutes 2004-10-28 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda-Approved. Minutes of 4/19/18-amended and approved. Consent item: from EPC expedited proposal from Hutchins – Approved. Information item: from EPC C- year-long "Golden four" GE courses. President report. From FSAC: Policy for Periodic Evaluation of Athletic Coaching Faculty and Revision to Periodic Evaluation of Temporary Faculty – Approved. Provost Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. Associated Students Report. From EPC: Syllabus policy (formally Course Outline Policy) – First Reading. From EPC: Temporary 48-unit GE Pattern – First Reading. APARC Report. Recommendation to endorse ATISS recommendation for new LMS – First Reading. Election of At-Large Members to the Executive Committee. APARC Priority Recommendations – Approved. EPC Report. SAC Report. Good of the Order.